Determinants of Dysfunctional Audit Behavior in the Public Accounting Firms - Mardi Mardi; Susi Indriani Sarka; Kardoyo Kardoyo (Shirkah: Journal of Economics and Business, 2022)
This study is an empirical examination of the determinants of dysfunctional audit behavior based on professional commitment and organizational commitment, as well as the turnover intention in a public accounting firm. Data were obtained from 100 auditors who have been registered as members of the Indonesian Institute of Certified Public Accountants (IICPA) with a minimum period of active duty of one year using online questionnaires. Data were analyzed using the Structural Equation Modelling with LISREL. This study concludes that organizational commitment and professional commitment have a negative effect on dysfunctional audit behavior and turnover intention. Commitment is crucial to avoiding dysfunctional audit behavior since persons who are committed are less likely to engage in such behavior. Conversely, the more the turnover intention, the higher the risk of dysfunctional audit behavior. Thus, it is suggested that auditors have emotional relationships, economic values, religious morals, and ethical attitudes when performing their duties as public accountants.